Psychology of interpersonal interaction - Kostruba, Nataliia (Lesya Ukrainka Volyn National University, 2022)
The course “Psychology of interpersonal interaction” belongs to the cycle of basic course of general education of a bachelor students. It is studied in the 4th semester, the form of control is a test. 3 of the credits (90 hours) are allocated for the study of the academic discipline, including: full-time study – 14 hours of lectures, 30 hours of seminars, 46 hours – independent work, 6 hours - consultations. The course is aimed at studying the patterns of personality formation and its socio-psychological development, features of group and interpersonal communication, the development of skills of effective interaction and communication.
Keywords: Communication; psychology; emotional regulation; conflict management; facilitation; mediation; arbitration